Search for pair production of vector-like quarks in the bW(b)over-barW channel from proton-proton collisions at root s=13TeV - KAYA, MİTHAT (ELSEVIER, 2018)
A search is presented for the production of vector-like quark pairs, T (T) over bar or Y (Y) over bar, with electric charge of 2/3(T) or -4/3(Y), in proton-proton collisions at root s= 13 TeV. The data were collected by the CMS experiment at the LHC in 2016 and correspond to an integrated luminosity of 35.8 fb(-1). The T and Y quarks are assumed to decay exclusively to a W boson and a b quark. The search is based on events with a single isolated electron or muon, large missing transverse momentum, and at least four jets with large transverse momenta. In the search, a kinematic reconstruction of the final state observables is performed, which would permit a signal to be detected as a narrow mass peak (approximate to 7% resolution). The observed number of events is consistent with the standard model prediction. Assuming strong pair production of the vector-like quarks and a 100% branching fraction to bW, a lower limit of 1295 GeV at 95% confidence level is set on the T and Y quark masses. (c) 2018 The Author(s). Published by Elsevier B.V.
Keywords: CMS; Physics; Vector-like quarks; HIGGS